1982
DOI: 10.1002/1097-0142(19821215)50:12<2956::aid-cncr2820501242>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic diagnosis of early gastric cancer by the endoscopic congo red-methylene blue test

Abstract: The endoscopic Congo red test combined with dyeing with methylene blue was performed in 85 patients with early gastric cancer (94 lesions). Results revealed that gastric cancer bleached the Congo red and methylene blue sprayed over their surface and this appeared in sharp contrast to the red‐colored mucosa of unaffected areas. Grossly, polypoid and flat types, and histologically differentiated adenocarcinomas bleached the dyes more frequently and more intensely than depressed and undifferentiated adenocarcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 6 publications
(3 reference statements)
2
16
0
Order By: Relevance
“…Above all, it is worth mentioning that the frequency of lymph node metastasis was similar in the two groups. Lymph node metastasis is the most reliable prognostic factor in gastric cancers when the depth of invasion is similar (Maruyama et al, 1987;Hioki et al, 1990;Maehara et al, 1992;Sano et al, 1992 Recent advances in diagnostic techniques allowed us to determine preoperative and intraoperative staging of gastric cancer (Tatsuta et al, 1982;Yasuda et al, 1986;Tio et al, 1989). In particular, endoscopic ultrasonography and intraoperative histological examination are useful for more objective determination of the depth of invasion for gastric cancer, which is strongly correlated with patients' survival time (Maruyama et al, 1989;Kitamura et al, 1996c).…”
Section: Methodsmentioning
confidence: 99%
“…Above all, it is worth mentioning that the frequency of lymph node metastasis was similar in the two groups. Lymph node metastasis is the most reliable prognostic factor in gastric cancers when the depth of invasion is similar (Maruyama et al, 1987;Hioki et al, 1990;Maehara et al, 1992;Sano et al, 1992 Recent advances in diagnostic techniques allowed us to determine preoperative and intraoperative staging of gastric cancer (Tatsuta et al, 1982;Yasuda et al, 1986;Tio et al, 1989). In particular, endoscopic ultrasonography and intraoperative histological examination are useful for more objective determination of the depth of invasion for gastric cancer, which is strongly correlated with patients' survival time (Maruyama et al, 1989;Kitamura et al, 1996c).…”
Section: Methodsmentioning
confidence: 99%
“…11,12 In addition, it is reported that a consecutive application with methylene blue enables distinction stomach areas altered by the tumor from their surroundings. 13 Therefore, in our study, Congo red is applied after application of indigo carmine. With this staining, carcinoma tissue was bleached out, while surrounding connective and muscle tissues were stained as brown-black.…”
Section: Discussionmentioning
confidence: 99%
“…In consecutive application with methylene blue, stomach areas altered by the tumor are bleached out, thus making them distinguishable from their surroundings. 8 In this study, Congo red was applied after indigo carmine. This consecutive staining enabled demarcation of the extent of tumor invasion; that is, carcinoma tissue was bleached out, while the surrounding connective and muscle tissues were stained brown-black.…”
Section: Discussionmentioning
confidence: 99%